Phenolic, flavonoid and anthocyanin contents of local sweet potato (Ipomoea batatas) - Shaari, Nurfarhana; Shamsudin, Rosnah; Mohd Nor, Mohd Zuhair; Hashim, Norhashila (Rynnye Lyan Resources, 2020)
The sweet potato (Ipomoea batatas) is an annual herb of the family Convolvulaceae and ranked as the world's seventh most important food crop with a major contribution to energy and phytochemical source of nutrition. Three different conditions of sweet potatoes are unpeeled tuber (UPSP), peeled tuber (PSP) and skin of tuber (SSP). The objective of this study is to evaluate the phytochemical availability (total phenolic contents (TPC), total flavonoid contents (TFC) and anthocyanin content) in the different parts of the sweet potato tuber. Folin-Ciocalteau (FC) assay showed that phenolic contents for UPSP (41.14±1.69 mg GAE/100 g dry basis) and PSP (42.24±2.19 mg GAE/100 g dry basis) were significantly (50%) higher than SSP (26.01±2.04 mg GAE/100 g dry basis). In terms of flavonoid content, the highest value was retained in PSP (9.55±0.82 mg quercetin/100 g dry basis) followed by UPSP (3.30±0.19 mg quercetin/100 g dry basis) and SSP (1.43 ± 0.03 mg quercetin/100 g dry basis). PSP (9.43±0.08 mg/100 dry basis) had a higher anthocyanin content compared to UPSP (5.21±0.02 b mg/100 g dry basis) and SSP (5.21±0.02 b mg/100 g dry basis). The phytochemical properties were available in all conditions of the sweet potato. However, PSP was suggested to be the most preferable condition for further processing in the sweet potato industry.